2007
DOI: 10.1002/ppul.20658
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sleep‐related hypoxia in primary school children

Abstract: Sleep-related hypoxia has adverse effects on cognition in children. Knowledge of factors contributing to sleep-related hypoxia is sparse. We aimed to identify demographic and clinical factors associated with mild (nadir arterial oxygen saturation 91-93%), moderate (nadir arterial oxygen saturation 3.9) sleep-related hypoxia in children. Parental questionnaires were distributed and overnight recordings of arterial oxygen saturation performed in a population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
8
1
1
Order By: Relevance
“…We should remark that there is limited information on the potential differences between obese and normal weight children in terms of ODI, particularly when taking into consideration the effect of SDB [25e27]. In one population-based study, overweight or obese children were at risk of having an elevated ODI 4, but no polysomnographic evaluation was performed to exclude nocturnal hypoxemia related to OSAS [27].…”
Section: Studies Reporting Reference Values For Nocturnal Pulse Oximementioning
confidence: 99%
“…We should remark that there is limited information on the potential differences between obese and normal weight children in terms of ODI, particularly when taking into consideration the effect of SDB [25e27]. In one population-based study, overweight or obese children were at risk of having an elevated ODI 4, but no polysomnographic evaluation was performed to exclude nocturnal hypoxemia related to OSAS [27].…”
Section: Studies Reporting Reference Values For Nocturnal Pulse Oximementioning
confidence: 99%
“…Oximetry seems less reliable in predicting the presence of OSA in obese children compared to normal-weight children. This could be attributed to the fact that overweight and obesity can be associated with the presence of sleep-related hypoxia even in the absence of OSA [7]. Also in patients with Down syndrome, oximetry seems to be less reliable as it has a higher night-to-night variability compared to other children [8].…”
Section: Introductionmentioning
confidence: 99%
“…47,[164][165][166][167] Fewer studies that included objective measurements to identify SDB were available. Two population-based studies using PSG demonstrated a relationship between overweight/obesity and OSAS.…”
Section: Epidemiology: Obesity As a Risk Factor For Snoring And Osasmentioning
confidence: 99%